Justification of the Importance of the Implementation of Digital Innovation Projects in the Food Service - Yu. V. Vylgina; M. Yu. Semakov (Informaciâ i Innovacii)
In the presented study, the trends in the digitalization of the processes of restaurant business objects are substantiated, existing approaches and classifications are presented. The authors have formed directions for the development of campaigns for the implementation of IT solutions to improve the efficiency of restaurants.